The Effect of Brand Image and Product Quality on Consumer Purchase Interest in Vaseline Products for Students of the Management Department of FEB UNISMUH Makassar - Aulia Aulia; Andi Mappatompo; Hasmiranda Hasmiranda (Universitas Muhammadiyah Makassar, 2024)
This study aims to: a) test the influence of brand image on consumer buying interest of Vaseline products in Management Department Students of FEB UNISMUH Makassar, b) test the effect of product quality on consumer buying interest of Vaseline products in Management Department Students of FEB UNISMUH Makassar. The population in this study is students majoring in Management, Faculty of Economics and Business, University of Muhammadiyah Makassar who buy and use Vaseline products. Because the population size is not yet known with certainty, Naresh K Malhotra's theory is used to determine the number of samples, which is as many as 105 respondents, but only 100 respondents can be analyzed.The type of data used in this study was descriptive quantitative obtained from questionnaires distributed to respondents. Based on the results of research using statistical calculations through the SPSS application version 25 regarding the influence of brand image and product quality on consumer buying interest, it shows that brand image has a positive and significant effect on consumer buying interest and product quality has a positive and significant effect on consumer buying interest.